Dynamics of the Insurance Paradigm Analysis in Pakistan: An Evidence of Leading Islamic, Public and Private Insurers - Ahmed , Shafiq; Afzal , Muhammad; Mughal, Khalid Mahmood (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper explores the dynamics of the general insurance paradigm throughout six different companies, NICL (National Insurance Company), EFU (Easter Federal Union), Adamjee, Jubilee General Insurance, Salaam Takaful Limited, and Pak-Qatar Takaful, in the developing economy of Pakistan from 2012 to 2021. To examine collective long-run outcomes, Pedroni and Kao tests were taken to measure the impact of public and private corporate entities as well as the cause-and-effect relation of each regressor on the dependent variable of solvency ratio, Granger causality and the Pooled Mean Group-Autoregressive Distributed Lag (PMG-ARDL) model have been used. According to the estimated outcomes, it has been deliberately observed that except for the claim ratio, all other explanatory variables positively influence the solvency ratio. In future, this paper will be help out researcher, practitioners, and public sector corporate consumer demand and service quality issues under the general insurance paradigm conventional and Islamic insurance as well.